Clayton Byrd goes underground - Williams-Garcia, Rita (Amistad, an imprint of HarperCollinsPublishers, 2017)
Feeling most alive when he's playing the blues with his grandfather, Clayton is devastated when his grandfather dies and his mother forbids him from playing music, losses that compel him to run away and join bluesmen on the road.